EFFECT OF LOADING FLUCTUATION ON EFFICIENCY BOILER PLTU UNIT I SOUTH MINAHASA - Permana, Dadang Suhendra (Universitas Mercu Buana, 2020)
Many aspects affect the performance of a power plant . One of her in the form of fluctuations in load of Control Center Interkoneksi expenses electricity network , as that occurred at the power plant Unit 1 South Minahasa. It is the possibility of big will air an influence on the efficiency of boiler power plant , which is now a reference in the assessment Performance Regulatory Base a steam power plant. Through the analysis of the effect of fluctuations in the workload of the Efficiency Boiler power plant Amurang Unit 1 Unit 1, the expected performance of the existing power plant can be in the know , s ehingga Performance Regulatory Base him untracked . Thus the energy saving effort will be achieved and at the same time encourage environmental preservation efforts. Because the Amurang PLTU Unit 1 uses medium rank coal / LRC which is environmentally friendly (low sulfur and ash content).